Olúdándè : estudo da normatização na estrutura de poder das casas-matrizes Iorubás, no Recife e em Salvador - Lima, Claudia Maria de Assis Rocha (2010)
The aim of this dissertation is to analyze the normalization of the power structure of the Yoruba parent homes, seeking elements in the complex historical process of the Yoruba group both in the African-Brazilian scenery and in the practices of the socio and political systems of Africa. The main focus of this study was to identify possible contours of the framework which delineates the African society in its governance and the construction of initiation rituals which allowed the ordination of houses of worship of traditional Yoruba in Brazil. Therefore, the observation of initiation practices in the parent homes of Yoruba tradition of Recife and Salvador formatted the liturgical process that gives legitimacy to practices which support the instance of the power of the African-Brazilian Yoruba priests, since this function does not exist with this curtailment of power in all socio religious African Yoruba setting outside the real. In this context, the dynamics of the research also identified possible sacred bonds of kinship between the two houses of worship investigated: Egba and Ketu